Reforming Labor Management Relations: Lessons from the Korean Experience 1996-97 - Se-il Park (Korea Development Institute (KDI), 2000)
This book critically examines the detail development of labor management relations reform in Korea which occurred during 1996 to 1997. It analyses such issues as why Korea launched labor management relations reform. What were the goals and objectives of the reform? How has it been initiated and implemented? What have been the major difficulties and obstacles and how has the reform leadership managed those adversities? In addition, the book evaluates the reform process from the perspective of effective reform management. How good has the reform managed? Has it been successful? If yes, how come?, if not, why not? What lessons can we draw from Korean experience? The author strongly believes that the Korean lessons can help in developing better strategies for successful reform both for the future Korea and for other developing nations. There have been many discussions and studies on what to reform in the developing nations, but very little studies on how to reform them successfully. In many cases, we know our goals but we do not know how to get there. We know what we have to do, but do not know how we can do it successfully. I am sure that this book will be an invaluable asset both for academics as well as practitioners.
Keywords: 330